Current Status and Future Prospects of the SNO+ Experiment. (24th January 2016) - Andringa, S.; Arushanova, E.; Asahi, S.; Askins, M.; Auty, D. J.; Back, A. R.; Barnard, Z.; Barros, N.; Beier, E. W.; Bialek, A.; Biller, S. D.; Blucher, E.; et al.
Abstract : SNO+ is a large liquid scintillator-based experiment located 2 km underground at SNOLAB, Sudbury, Canada. It reuses the Sudbury Neutrino Observatory detector, consisting of a 12 m diameter acrylic vessel which will be filled with about 780 tonnes of ultra-pure liquid scintillator. Designed as a multipurpose neutrino experiment, the primary goal of SNO+ is a search for the neutrinoless double-beta decay (0ν β β ) of 130 Te. In Phase I, the detector will be loaded with 0.3% natural tellurium, corresponding to nearly 800 kg of 130 Te, with an expected effective Majorana neutrino mass sensitivity in the region of 55–133 meV, just above the inverted mass hierarchy. Recently, the possibility of deploying up to ten times more natural tellurium has been investigated, which would enable SNO+ to achieve sensitivity deep into the parameter space for the inverted neutrino mass hierarchy in the future. Additionally, SNO+ aims to measure reactor antineutrino oscillations, low energy solar neutrinos, and geoneutrinos, to be sensitive to supernova neutrinos, and to search for exotic physics. A first phase with the detector filled with water will begin soon, with the scintillator phase expected to start after a few months of water data taking. The0 ν β β Phase I is foreseen for 2017.